Ovine clone ST1464: A predominant genotype of Staphylococcus aureus subsp. anaerobius isolated from sheep in Sudan - Haitham Elbir; Edward J. Feil; Michel Drancourt; Véronique Roux; Sulieman M El Sanousi; Mona Eshag; Patricia Colque-Navarro; Inger Kühn; Jan-Ingmar Flock (Journal of Infection in Developing Countries)
Background: The aim of the present study was to examine the phenotypic and genotypic relatedness of 17 Staphylococcus aureus subsp. anaerobius isolates recovered from sheep abscesses in Khartoum state, Sudan, during the period 2007-2008.